Can the magnetic susceptibility record of Chinese Red Clay sequence be used for palaeomonsoon reconstructions?. Issue 3 (8th January 2016) - Zhao, Guoyong; Han, Yan; Liu, Xiuming; Chang, Liao; Lü, Bin; Chen, Qu; Guo, Xuelian; Yan, Junhui; Yan, Jun
Abstract: Red Clay underlying the loess-palaeosol sequences on the Chinese Loess Plateau is an eolian deposit. There is a controversy over whether magnetic susceptibility ( χ ) variations in Red Clay sequence can be used as an indicator of summer palaeomonsoon intensity. This study investigates the magnetic mineralogy, magnetic concentration and magnetic grain size distribution of Jiaxian Red Clay with multimagnetic methods. Our results indicate that the magnetic properties of Jiaxian Red Clay are similar to those of the Quaternary loess-palaeosol sequences, and ultrafine ferrimagnetic grains produced during pedogenesis are responsible for an increase in susceptibility, therefore the χ enhancement mechanism of Red Clay is similar to that of the overlying loess-palaeosol sequences. This paper explores χ variations in the Red Clay sequence through spatial and temporal analysis. The susceptibility variation of six sites along a NNE to SSW transect correlate to palaeoclimatic cycles, so χ can be used to trace the summer palaeomonsoon intensity from a spatial perspective. However, a simple loess-derived calibration function cannot be used to quantitative reconstruct the palaeomonsoon intensity variations thought time. An adjusted calibration function for palaeosols from Red Clay sequence needs to be developed, so that χ can be used to quantitative reconstruct palaeomonsoon intensity. Further study is necessary to develop such a transfer function.